Conceptually mapping how investing in essential public health functions (EPHFs) and common goods for health (CGH) can improve health system performance - Amri, Michelle; Rajan, Dheepa; Koch, Kira; Earle, Alexandra J.; Sparkes, Susan P.; Zhang, Yu; Saikat, Sohel; Bump, Jesse B. (Frontiers in Public Health, 2025)
BackgroundCalls for investing in essential public health functions (EPHFs) and common goods for health (CGH) are numerous, but it is often unclear to policymakers how such investments lead to health system improvements.ObjectivesTo showcase plausible pathways between actions taken to improve specific health system functions—in other words, investments in EPHFs and CGH—and their impact on health system performance, the health systems performance assessment framework for Universal Health Coverage is used. We draw on three examples—community engagement and social participation, taxes and subsidies, and public health surveillance and monitoring—to demonstrate how action in these areas can improve health systems.ConclusionsThis conceptual mapping also points to the crucial role of good governance and demonstrates how investing in multiple EPHFs and CGH can trigger a chain reaction to spur broader health system improvement.